Editorial: Strengths and Flaws of Aging Policies in Canada/ Les forces et les faiblesses des politiques du vieillissement au Canada - Matsuoka, Atsuko; Beaulieu, Marie; Kitchen, Brigitte (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2013)
The guest editors would like to thank Shamette Hepburn for her help with the picture used for the editorial.